An empirical study of process knowledge: coherence as a static process property. Issue 4 (24th August 2012) - Crabtree, Carlton A.; Norcio, Anthony F.; Seaman, Carolyn B.
ABSTRACT: This paper presents our research experiences studying process knowledge with qualitative and quantitative methods. Informed by related arguments, we present two hypotheses that are tested using a between subjects experimental design. The first hypothesis concerns the accuracy of software process elicitation, which we characterize as the human perception of error between description and performance of a process. The second hypothesis explores the detection of subtle differences in process articulation using latent semantic analysis, a computational technique for measuring patterns in written discourse. The results of our analyses are compared along with discussion of theoretical implications. We define a new type of process property, Coherence, which represents a measure of relatedness in process knowledge. Results also indicate that Coherence may be increased with the use of a conceptual model. Future research is guided by experimental and industrial application. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : This paper presents our research experiences studying process knowledge with qualitative and quantitative methods. Informed by related arguments, we present two hypotheses which are tested using a between subjects experimental design. We define a new type of process property, Coherence, which represents a measure of relatedness in process knowledge. Results also indicate that Coherence may be increased with the use of a conceptual model. Future research is guided by experimental and industrial application.